Science and medicine applied to soccer refereeing: An update - Weston, M.; Castagna, C.; Impellizzeri, F. M.; Bizzini, M.; Williams, A. M.; Gregson, W. (Sports Medicine, 2012)
Soccer referees are required to keep up with play at all times to ensure optimal positioning in making key decisions. While the physiological aspects of soccer refereeing have been extensively reviewed, other key areas of preparation and performance have yet to be considered in detail. We present a contemporary examination of methodological considerations for the interpretation of referees' match activities, the validation of fitness testing and training protocols, match and training injury profiles, and the understanding and development of perceptual-cognitive expertise.